2017
DOI: 10.1371/journal.pone.0182062
|View full text |Cite
|
Sign up to set email alerts
|

Lengthening of knee flexor muscles by percutaneous needle tenotomy: Description of the technique and preliminary results

Abstract: BackgroundKnee flexion contractures occur frequently in non-ambulatory, aged persons and persons with central nervous system lesions, rendering positioning and nursing care difficult. There are often risks associated with surgical interventions.ObjectiveTo evaluate the effectiveness of percutaneous needle tenotomy to lengthen the knee flexor muscles and improve passive function.MethodsThis was a retrospective study of all patients who underwent percutaneous needle tenotomy between 2012 and 2014. Tenotomy was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Schnitzler, et al performed a retrospective study treating knee flexion contracture with percutaneous needle tenotomy for tendon lengthening. 16 Overall, the treatment was well tolerated with significantly increased range of motion. Another study evaluated flexion contractures after total knee arthroplasty and found success with bone resection and subsequent posterior capsule and collateral ligament release.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Schnitzler, et al performed a retrospective study treating knee flexion contracture with percutaneous needle tenotomy for tendon lengthening. 16 Overall, the treatment was well tolerated with significantly increased range of motion. Another study evaluated flexion contractures after total knee arthroplasty and found success with bone resection and subsequent posterior capsule and collateral ligament release.…”
Section: Introductionmentioning
confidence: 86%
“…A few studies have reported on surgical treatments for flexor tendon contracture, especially in the knee. Schnitzler, et al performed a retrospective study treating knee flexion contracture with percutaneous needle tenotomy for tendon lengthening 16 . Overall, the treatment was well tolerated with significantly increased range of motion.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous soft tissue lengthening with an intramuscular needle has been previously described in the treatment of other diseases, such as Dupyutren's contracture of the hand [12], tendinitis [13,14], epicondylitis [15], and congenital talipes equinovarus [16,17], as well as for muscle contractures at different locations [18][19][20][21]. However, we are not aware of any publication describing the application of this technique in pediatric patients with equinus ankle.…”
Section: Introductionmentioning
confidence: 99%